Care for care: Studio REV-'s strategies of engagement. Issue 1 (1st December 2015) - Coombs, Gretchen
The artists at Studio REV-, along with their allies in the broader non-profit sector, address domestic workers' rights in the United States. As a social practice art project, NannyVan works to improve how information about domestic rights is disseminated to these workers, whether nannies, elder caregivers or others. As part of a larger project named CareForce, the NannyVan project shows an ethics of care by using design traces as tactics and transversal methods as strategies.